The Impact of the Sense of Security from Crime on Residential Property Values in Brazilian Metropolitan Areas - David M. Vetter; Kaizô I. Beltr\~ao; Rosa M. R. Massena (Inter-American Development Bank (IDB), 2013)
Using a hedonic residential rent model for Brazil's metropolitan areas calibrated with microdata from Brazil's annual household survey, this study estimates that increasing the sense of security in the home by one standard deviation would increase average home values by R1,513 (US757), or about US13. 6 billion if applied to all 18. 0 million households in the study area. The principal components analysis of sense of security and crime victimization variables indicates that higher-income households feel more secure from crime in the home, even though theft and robbery victimization rise with household income and rent level. Higher levels of home protection measures by higher-income households partially explain this result.
Keywords: C83; R23; R31; 330